Application of Lean Manufacturing Principles to increase machine availability in Peruvian SMEs in the textile sector - Palpan Curisinche, Isaac Daniel (2022)
Based on figures in the textile industry over the past years, it can be assumed currently that this industry is one of the most important markets in different countries because of high consumption. Due to economic value and the increasing work activities in the textile sector is related to the last trends in fashion. However, there are still challenges to overcome for instance: low availability of machines or poor human resources management generate economic and productive impacts. Within this context, it arises the need to propose an integrated model combining Total Productive Maintenance (TPM) and Lean Leadership which supports and creates a synergy between maintenance management and human resources; by using tools such as the orders and maintenance plan, system simulation in two comparative scenarios, a continuous system assessment combined with 5S methodology, and providing education and training in good practices in lean Leadership. Thereafter, the model was implemented, the availability indicator was calculated to attack the main problem and as result, it had an increase of 10.56%, this increase supports optimally and validates the proposal of the present study.